2020
DOI: 10.1016/j.neuroscience.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Enduring Effects of Social Deprivation during Adolescence in Rats: Implications for Psychiatric Disorders

Abstract: The exposure to adverse environmental situations during sensitive periods of development may induce re-organizational effects on different systems and increase the vulnerability to develop psychiatric disorders later in life. The adolescent period has been demonstrated extremely susceptible to stressful events. However, most of the studies focused on the immediate effects of stress exposure and few of them investigated sex differences. This raised the question if these modulations might also be long-lasting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Moreover, exposure of rodents to an early-life social challenge may increase the sensitivity to the effects of psychostimulant drugs, among which amphetamine, determining an exacerbation of the hyperactivity state [ 103 , 104 ]. Furthermore, social isolation may induce a persistent anhedonic-like phenotype [ 105 , 106 ], with a disruption of sensorimotor gating, a measure of the ability to integrate cognitive and sensory inputs, as well as a deficit in novel object discrimination paradigm [ 107 , 108 ], reflecting attention and memory dysfunctions. The behavioral alterations following stress in adolescence are associated with different neurochemical and molecular changes.…”
Section: Stress Exposure and Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, exposure of rodents to an early-life social challenge may increase the sensitivity to the effects of psychostimulant drugs, among which amphetamine, determining an exacerbation of the hyperactivity state [ 103 , 104 ]. Furthermore, social isolation may induce a persistent anhedonic-like phenotype [ 105 , 106 ], with a disruption of sensorimotor gating, a measure of the ability to integrate cognitive and sensory inputs, as well as a deficit in novel object discrimination paradigm [ 107 , 108 ], reflecting attention and memory dysfunctions. The behavioral alterations following stress in adolescence are associated with different neurochemical and molecular changes.…”
Section: Stress Exposure and Schizophreniamentioning
confidence: 99%
“…Challenges occurring during adolescence may also induce disruptions in neuroplasticity-related markers. Accordingly, we have recently demonstrated that adolescent social isolation in male rats determines a selective reduction of Bdnf mRNA levels within the prefrontal cortex, but not the hippocampus [ 105 ]. Moreover, isolation rearing can impair the HPA axis functionality, highlighting the strong impact on stress-related responses.…”
Section: Stress Exposure and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Stress during development is generally thought to evoke negative behavioral effects later in life (27,28,(30)(31)(32)(33)(34)(35). However, prior studies also support the ability of adolescent stress to confer stress resilience in adulthood, using a number of stress models (reviewed in 11,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Stress modality may also play a role in the development of resilience. For instance, complete social isolation during adolescence increases anxiety-like behavior, acoustic startle and impaired extinction in adulthood (47), whereas social instability (PND [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], that entails poor social structure but no isolation, evokes a reduction of conditioned fear expression in adulthood (48). The same protocol of social instability proved to be less effective in female rats (49), pointing to possible sex-dependent mechanisms for the programming of the long-term effects of adolescent stress, consistent with our observed sex differences.…”
Section: Discussionmentioning
confidence: 99%